Early Responses: An Introduction. Issue 4 (21st April 2021) - Deppermann, Arnulf; Mondada, Lorenza; Doehler, Simona Pekarek
ABSTRACT: This special issue investigates early responses—responsive actions that (start to) unfold while the production of the responded-to turn and action is still under way. Although timing in human conduct has gained intense interest in research, the early production of responsive actions has so far largely remained unexplored. But what makes early responses possible? What do such responses tell us about the complex interplay between syntax, prosody, and embodied conduct? And what sorts of actions do participants accomplish by means of such early responses? By addressing these questions, the special issue seeks to offer new advances in the systematic analysis of temporal organization in interaction, contributing to broader discussions in the language and cognitive sciences as to the social coordination of human conduct. In this introductory article, we discuss the role of temporality and sequentiality in social interaction, specifically focusing on projective and anticipatory mechanisms and the interplay between multiple semiotic resources, which are crucial for making early responses possible.